In situ bioassay chambers and procedures for assessment of sediment toxicity with Chironomus riparius - Castro, Bruno B. (2003)
The purpose of this study was to develop an in situ sediment bioassay chamber and respective procedures, suitable for performing toxicity bioassays with benthic invertebrates, using the midge Chironomus riparius. It was also our objective to compare the responses obtained under controlled conditions (laboratory 10-day larval growth and survival test) with those obtained in situ. Clean sand and a formulated sediment were incorporated in the in situ bioassay, along with local sediments, as a way of minimizing natural variability due to physicochemical differences among sediments or due to interactions with indigenous organisms. Recovery of organisms was good (80-100% in the control and reference site), indicating that the developed chamber and protocol were suitable for exposing and retrieving C. riparius in situ. Results also showed differences between responses obtained with formulated and natural sediment in situ, as well as between laboratory and in situ.